The Effect of Hard Chine Planing Variations on Resistance and Stability of a Patrol Boat Hull - Dani, Fildan Lujainid; Raharja, Achmad Mukti; Sihombing, Herawaty Magdalena; Abadi, Galang Wahyu (Naval Architecture Department, Kalimantan Institut of Technology, 2025)
Patrol boat play a crucial role in maritime security and law enforcement, where optimizing hull performance is essential to achieve both efficiency and stability in various sea states. This study analyzes the influence of hard chine variations on the resistance and stability of a patrol boat hull. Four hull models single and double chine with angles of 0° and 10° were evaluated using Maxsurf Resistance and Stability. Total resistance was calculated at service speeds of 10 and 15 knots, while stability was assessed based on IMO Resolution A.749(18), Chapter 3. Results show that at 10 knots, the single chine 10° model produced the lowest resistance, whereas at 15 knots, the double chine 10° gave the best performance. Stability analysis indicated that all models met IMO criteria, with the double chine 10° achieving the highest GMt, maximum GZ, and angle of maximum GZ. The findings suggest that the single chine 10° is more efficient for calm-water operations, while the double chine 10° provides superior stability for rough-sea conditions